Efficiencies and mechanism of enhanced coagulation pre-treatment on domestic sewage with PAC-HCA compound - Yan, Zichun (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Poly dimethyl diallyl propyl ammonium chloride (HCA) and poly aluminum chloride (PAC) were used to prepare complex coagulants for the enhanced coagulation (EC) pretreatment of domestic sewage. The influences of hydraulic conditions, the dosage ratio of PAC-HCA complex coagulants, initial pH value, and dosage on the removal efficiency of SS, COD, and TP in domestic sewage were investigated. The fractal dimension and Zeta potential were used to verify and characterize the experimental results. The results showed that the optimum coagulant conditions were as follows: G1 = 200.0-265.0 s-1, T1 = 1.5 min, G2 = 40.0 s-1, T2 = 5 min, PAC: HCA = 25:1, dosage = 15 mL/L, pH = 8. At the mentioned point, the removal rates of SS, COD, and TP are 98.74%, 44.63%, and 89.85%, respectively. In addition, through comparative tests, PAC-HCA compound coagulants show better treatment efficiency than PAC and HCA used alone. When the HCA dosage was 15 mg/L, Zeta potential and flocs fractal dimension was 2.29 mv and 0.9844, respectively. This indicates that PAC-HCA has a good treatment effect on domestic sewage, and the mechanism of enhanced coagulation to remove nutrients is mainly electrical neutralization